Health inequalities in European cities: perceptions and beliefs among local policymakers. Issue 5 (28th May 2014) - Morrison, Joana; Pons-Vigués, Mariona; Bécares, Laia; Burström, Bo; Gandarillas, Ana; Domínguez-Berjón, Felicitas; Diez, Èlia; Costa, Giuseppe; Ruiz, Milagros; Pikhart, Hynek; Marinacci, Chiara; Hoffmann, Rasmus; et al.
Abstract : Objective: To describe the knowledge and beliefs of public policymakers on social inequalities in health and policies to reduce them in cities from different parts of Europe during 2010 and 2011. Design: Phenomenological qualitative study. Setting: 13 European cities. Participants: 19 elected politicians and officers with a directive status from 13 European cities. Main outcome: Policymaker's knowledge and beliefs. Results: Three emerging discourses were identified among the interviewees, depending on the city of the interviewee. Health inequalities were perceived by most policymakers as differences in life-expectancy between population with economic, social and geographical differences. Reducing health inequalities was a priority for the majority of cities which use surveys as sources of information to analyse these. Bureaucracy, funding and population beliefs were the main barriers. Conclusions: The majority of the interviewed policymakers gave an account of interventions focusing on the immediate determinants and aimed at modifying lifestyles and behaviours in the more disadvantaged classes. More funding should be put towards academic research on effective universal policies, evaluation of their impact and training policymakers and officers on health inequalities in city governments.